2017
DOI: 10.1523/eneuro.0144-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Correlation Structure Supporting a Rate-Code for Sound Localization in the Owl’s Auditory Forebrain

Abstract: While a topographic map of auditory space exists in the vertebrate midbrain, it is absent in the forebrain. Yet, both brain regions are implicated in sound localization. The heterogeneous spatial tuning of adjacent sites in the forebrain compared to the midbrain reflects different underlying circuitries, which is expected to affect the correlation structure, i.e., signal (similarity of tuning) and noise (trial-by-trial variability) correlations. Recent studies have drawn attention to the impact of response cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 116 publications
(210 reference statements)
1
9
1
Order By: Relevance
“…This criterion led to five pairs of neurons being omitted; however, all neurons had at least one usable pair (n = 194 original pairs, 189 usable pairs). Nearby neurons in OT fired synchronously, as previously reported (Beckert et al, 2017). As predicted by the model, synchrony (assessed by the standard-CCG) was correlated with the GM firing rate both across the sampled population (r = 0.31; p , 0.0001; two-tailed t test; Fig.…”
Section: Stimulus-dependent Synchrony In Otsupporting
confidence: 82%
See 2 more Smart Citations
“…This criterion led to five pairs of neurons being omitted; however, all neurons had at least one usable pair (n = 194 original pairs, 189 usable pairs). Nearby neurons in OT fired synchronously, as previously reported (Beckert et al, 2017). As predicted by the model, synchrony (assessed by the standard-CCG) was correlated with the GM firing rate both across the sampled population (r = 0.31; p , 0.0001; two-tailed t test; Fig.…”
Section: Stimulus-dependent Synchrony In Otsupporting
confidence: 82%
“…We therefore hypothesize that binaural cue-dependent synchrony in ICcl underlies binaural cue-dependent synchrony downstream to ICx. Lastly, stimulus-dependent synchrony could be inherited from ICx to OT through the known shared point-topoint projections between these structures (Knudsen and Knudsen, 1983;Beckert et al, 2017). Simultaneous recording of nearby ICcl and ICx cells has proven challenging due to large evoked potentials corrupting spike sorting (Beckert MV and Pena JL unpublished observations).…”
Section: Stimulus-dependent Synchrony In Otmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the owl's forebrain have reported evidence of a transformation in the neural code of ITD, where convergence across ITD channels leads to quasi-hemispherical ITD tuning Wagner, 2009, 2012). Furthermore, recent comparative population recordings in the owl's midbrain and forebrain showed differing correlation structure of nearby cells, where the hemispherical tuning of forebrain cells was associated with a significant drop in correlated variability of nearby cells, eliminating the potentially detrimental effect of noise correlation on information in a putative forebrain opponent-channel code (Beckert et al, 2017).…”
Section: New Evidence On the Coding Of Itd In The Owl's Midbrain And Forebrainmentioning
confidence: 96%
“…Transformation of the representation of ITDs may take place after the detection level (for review, see Vonderschen and Wagner, 2014). For example, there is evidence that in the owl forebrain a hemispheric rate code is realized (Beckert et al, 2017) in contrast to an ITD map in its midbrain (Wagner et al, 1987).…”
Section: Maps In Nlmentioning
confidence: 99%